461 Radiological Assessment of Capital Realignment Surgery following Slipped Capital Femoral Epiphyses (Scfe). (October 2012) - Keith, T; Balakumar, J
Abstract : Introduction: The pinning in situ of slipped capital femoral epiphysis (SCFE) is the accepted gold standard treatment. However the resultant deformity from pinning of severe SCFE creates an altered femoral head-neck relationship. This contributing to femoroacetabular impingement and eventually the development of osteoarthroses. 1 The principal investigator has previously published on the use of two radiographic indices, alpha angle and displacement from Kleins line, surrogates of impingement, to evaluate the femoral head neck relationship in mild to moderate grade severity SCFE's. treated by pinning in situ. 2 Subcapital realignment surgery through surgical hip dislocation has been performed in moderate to severe SCFE in an attempt to restore femoral head neck geometry. 3 We describe the use of the two previously recognised radiographic parameters in the setting of capital realignment for the treatment of severe SCFE. Aims: To assess the radiological outcomes; alpha angle, and displacement from Klein's line in patients having undergone capital realignment, compared with normative data. Methods: We retrospectively reviewed 11 patients (6 males, 5 females mean age 12.2 years with moderate to severe (1 moderate: 10 severe) SCFE having undergone capital realignment between 2009 and 2011. Results: Alpha angles restored to normal range in all patients. Klein's line offset was restored to positive displacement in 7 patients, with 3 patients noted to demonstrate a new radiographic finding termed pistol grip type deformity. Discussion: The radiographic parameters of alpha angle and Klein's line offset are useful in quantifying the restoration of proximal femoral anatomy following capital realignment.